Persistent neurocognitive impairments associated with severe falciparum malaria in Kenyan children. Issue 4 (16th March 2005) - Carter, J A; Mung'ala-Odera, V; Neville, B G R; Murira, G; Mturi, N; Musumba, C; Newton, C R J C
Abstract : Objectives: There is little information on the characteristics of persisting impairments associated with severe forms of falciparum malaria. Previous work has suggested the existence of a group of children with particularly poor performance on neurocognitive assessments in the context of average group performance. The aim of this study was to provide a detailed characterisation of impairments in this subgroup. Methods: Three groups of children were recruited: children admitted up to nine years earlier with cerebral malaria (CM) (n = 152), malaria and complicated seizures (M/S) (n = 156), or those unexposed to either condition (n = 179). Each child underwent a series of developmental assessments. Standard definitions were used to classify impairment. Results: Twenty four percent of the CM and M/S groups had at least one impairment in the major domains assessed in the study, compared with 10% of the unexposed group. CM was associated with a higher proportion of multiple impairments and an increased risk of mortality in the first year after recovery in those identified with impairments on discharge. Conclusions: After severe malaria, some children have neurocognitive impairments that are evident as long as nine years later. Impairments may become more evident as children progress and face more complex cognitive and linguistic demands, socially and educationally. The child's neurological status at discharge was not a good predictor of later neurocognitive impairment. This highlights the importance of follow up for children with severe malaria and the involvement of therapists and educators in the provision of services for this population.